1999
DOI: 10.1007/s002130050858
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tryptophan depletion and loading on laboratory aggression in men: time course and a food-restricted control

Abstract: Some studies have shown that sharp reduction of L-tryptophan (Trp) concentration in plasma results in increases in laboratory-measured aggression. Conversely, raising plasma Trp has blunted aggression. These effects are presumably due to impaired or enhanced serotonin synthesis and neurotransmission in the brain. In this study, the laboratory-measured aggressive behavior of eight men under both Trp depletion (T-) and Trp loading (T+) conditions was compared to their aggressive behavior under food-restricted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 33 publications
(41 reference statements)
6
67
0
5
Order By: Relevance
“…Other studies using normal males have reported conflicting results under Trp depletion (Bjork et al 1999;Moeller et al 1996;Pihl et al 1995;Smith et al 1986); for example, high-trait aggressive men have shown increases in both subjective paperand-pencil measures and in laboratory-measured behavioral aggression under Trp depletion, whereas lowtrait aggressive men have not (Cleare and Bond 1995). In our most recent laboratory studies (Bjork et al 1999(Bjork et al , 2000, Trp depletion increased aggressive behavior in men with high baseline levels of aggression but did not affect men with low baseline levels.Most studies of the relationship between CNS 5-HT function and aggressive/impulsive behaviors have relied on men. In our laboratory, we are conducting a series of systematic analyses of aggressive/impulsive behavior of women using a paradigm (PSAP, see below) to prospectively measure changes in aggressive responding as a result of experimental manipulation.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Other studies using normal males have reported conflicting results under Trp depletion (Bjork et al 1999;Moeller et al 1996;Pihl et al 1995;Smith et al 1986); for example, high-trait aggressive men have shown increases in both subjective paperand-pencil measures and in laboratory-measured behavioral aggression under Trp depletion, whereas lowtrait aggressive men have not (Cleare and Bond 1995). In our most recent laboratory studies (Bjork et al 1999(Bjork et al , 2000, Trp depletion increased aggressive behavior in men with high baseline levels of aggression but did not affect men with low baseline levels.Most studies of the relationship between CNS 5-HT function and aggressive/impulsive behaviors have relied on men. In our laboratory, we are conducting a series of systematic analyses of aggressive/impulsive behavior of women using a paradigm (PSAP, see below) to prospectively measure changes in aggressive responding as a result of experimental manipulation.…”
mentioning
confidence: 62%
“…Studies have shown that men reporting higher hostility and aggression levels (paper-and-pencil measures) also have higher baseline levels of plasma Trp (Eriksson and Lidberg 1997;Møller et al 1996;Virkkunen and Närvänen 1987;Wingrove et al 1999). Other studies using normal males have reported conflicting results under Trp depletion (Bjork et al 1999;Moeller et al 1996;Pihl et al 1995;Smith et al 1986); for example, high-trait aggressive men have shown increases in both subjective paperand-pencil measures and in laboratory-measured behavioral aggression under Trp depletion, whereas lowtrait aggressive men have not (Cleare and Bond 1995). In our most recent laboratory studies (Bjork et al 1999(Bjork et al , 2000, Trp depletion increased aggressive behavior in men with high baseline levels of aggression but did not affect men with low baseline levels.…”
mentioning
confidence: 99%
“…This indirectly supports the lack of effect of serotonin in the control of stopping because there are links between serotonin and some, although not all, forms of aggression. For example, serotonin depletion using ATD may increase aggression in subjective assessment and in laboratory tests such as the Point Subtraction Aggression Paradigm and Taylor Competitive Reaction Time Task (Bjork et al 1999(Bjork et al , 2000Cleare and Bond 1995;Moeller et al 1996;Pihl et al 1995;Salomon et al 1994).…”
Section: Role Of 5-ht In Action Cancellationmentioning
confidence: 99%
“…9 Studies examining inhibition of serotonin biosynthesis, either in individuals with tryptophan hydroxylase enzyme polymorphism 26 or in those in whom tryptophan is removed from the diet, 3 have found significant increases in aggressive behavior associated with low levels of serotonin. Traditional treatment for IED may include behavioral therapy, pharmacotherapy, or a combination.…”
Section: Nonsurgical Therapies For Iedmentioning
confidence: 99%